Technology and Sexual Health: A discussion on e-Health tools for the promotion of sexual and reproductive care - Pieramico, Sonia (Technium Social Sciences Journal, 2022)
Along the present discussion we debate the implementation of e-Health in context of sexual health using information on various recent digital tools. Considering the information collected, there are various challenges that come with such new technologies, but accessibility, low costs and several positive outcomes seem to count for the further development and integration of e-Health in sexual health care. Furthermore, promoting a safe and positive sex life among various populations, even the ones harder to access, may promote gender equality, socioeconomic disparities and literacy on sexuality.